2017
DOI: 10.3892/ol.2017.7466
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic action of methylquercetins in human lung adenocarcinoma cells

Abstract: Abstract. Lung cancer is the malignant disorder associated with a high number of fatalities in women and men worldwide. Despite continuous improvements in diagnostic strategies and therapeutic modalities over the past decades, the prognosis and survival rate of patients suffering from lung cancer are still unsatisfactory and suggest the requirement for further molecular studies with different lung cancer models. In the present study, the anticancer action of two methylated metabolites of quercetin, isorhamneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…According to the literature, 4-keto-pinoresinol was reported to be active against SK-Mel-2, B16F1, ovarian cancer SKOV-3, CaoV-3, and cervical cancer HeLa cell lines cycle [ 17 ]. Tamarixetin was previously reported to possess cytotoxic action against A-549 and HCC-44 lung adenocarcinoma cells, gastric carcinoma (AGS), skin melanoma (B16F10), brain carcinoma (C6), epitheliod cervix carcinoma (HeLa) cells, MCF-7 and HCT-116 cells [ 18 , 19 , 20 ]. Additionally, 3,4-dihydrozybenzoic acid was also reported to cause apoptosis on human breast cancer MCF-7 cell, lung cancer A-549 cell, HepG2 cell, cervix HeLa cell, prostate cancer LNCaP cell, and A549 human lung cancer [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, 4-keto-pinoresinol was reported to be active against SK-Mel-2, B16F1, ovarian cancer SKOV-3, CaoV-3, and cervical cancer HeLa cell lines cycle [ 17 ]. Tamarixetin was previously reported to possess cytotoxic action against A-549 and HCC-44 lung adenocarcinoma cells, gastric carcinoma (AGS), skin melanoma (B16F10), brain carcinoma (C6), epitheliod cervix carcinoma (HeLa) cells, MCF-7 and HCT-116 cells [ 18 , 19 , 20 ]. Additionally, 3,4-dihydrozybenzoic acid was also reported to cause apoptosis on human breast cancer MCF-7 cell, lung cancer A-549 cell, HepG2 cell, cervix HeLa cell, prostate cancer LNCaP cell, and A549 human lung cancer [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported cytotoxic against MCF-7 cells (70), and induced apoptosis in HepG2 cells (71). Methylquercetin was reported for antimigration and antiproliferative activities(72), while Sak et al (73) reported high cytotoxicity of its analogues 3'-O-methylquercetin Unknown -The major compounds are written in bold and 4'-O-methylquercetin against A549 and HCC-44 cell lines. Both analogues exhibited higher activity (IC 50 of 26.6 µmol/L and 19.6 µmol/L against A549 and 15.9 µmol/L and 20.3 µmol/L against HCC-44, respectively) than quercetin (72.2 µmol/L and 107.6 µmol/L, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the anti-cancer effects of isorhamnetin in various cancer cell lines have been shown to involve the death receptor (DR)-dependent extrinsic and/or mitochondria-dependent intrinsic pathways [19,24,27,28,29,30,31], which are representative apoptosis inducing pathways. It was also found that the anti-cancer effect of isorhamnetin was accompanied by the disturbance of various cellular signaling pathways [20,25,32].…”
Section: Introductionmentioning
confidence: 99%